PENGEMBANGAN SISTEM INFORMASI MANAJEMEN UNTUK MENINGKATKAN EFISIENSI OPERASIONAL PADA ORGANISASI PUBLIK - Adelia Amri; Muhammad Irwan Padli Nasution (INTERNATIONAL, Journal of Sharia Business Management, 2025)
The development of Management Information Systems (MIS) has become a critical component in enhancing operational performance and modernizing public sector administration. As public organizations face increasing pressure to deliver transparent, accountable, and high-quality services, MIS serves not only as a technological upgrade but also as a strategic governance mechanism. This journal critically examines the role of MIS in improving transparency, strengthening financial and administrative accountability, and elevating service delivery standards within public institutions. Utilizing a descriptive qualitative approach supported by literature analysis, the study underscores that technology alone is insufficient to generate meaningful institutional improvement. The findings reveal that the successful implementation of MIS is largely determined by the integration of three core dimensions: technological infrastructure, human resource capacity, and policy alignment. Without organizational readiness, cultural adaptation, and adequate digital competence, MIS adoption risks becoming a symbolic formality with limited operational impact. Accordingly, continuous capacity building, user-centered system design, and strong leadership commitment are required to ensure sustainability. The study concludes that MIS should be viewed not merely as a digital reporting platform, but as a transformational instrument capable of reshaping public management practices toward greater efficiency, transparency, and responsiveness to public needs